Solving a social dilemma using behaviourally framed text messaging to increase school fees contribution in public schools in South Africa - Titus, Emilio (School of Economics, 2022)
This paper presents the results from a randomised controlled trial conducted in two Section 21 schools in Cape Town, South Africa, to test whether text messages can improve the fee-payment behaviour of parents. Parents who were randomly assigned to one of two treatment groups received a monthly behaviourally framed message reinforcing the affective and financial benefits of education. Included in the message is a prompt to pay school fees by the month-end due date. Parents were segmented into those who historically pay fees well (Cooperators) and those who pay inconsistently or don't pay any fees at all (Defectors). The results show that parents in the cooperator group, respond positively to both affective and finance framed messages, and they pay between 1% and 5.2% more than parents who received just a reminder or no message. Surprisingly, the parents in the Defector group respond negatively to the affective and finance-framed messages and they pay up to 14% less than parents who received a reminder message or no message. The learning here is that text messaging can make things worse, so be careful! The paper also confirmed that Cooperators pay a higher proportion of their school fees compared to Defectors, and the level of defection is strongly influenced by how well other parents are paying their fees, especially if many parents are benefiting from a fee exemption, or are just not paying any school fees. Text messaging to promote cooperative parental fee payment behaviour shows promise as a low-cost mechanism that can be used by schools towards sustaining the financial robustness of existing Section 21 schools. Going forward, its efficacy can be tested by experimenting with different messages that can connect with the fee-paying preferences of Defectors and possibly help to improve the financial situation in schools that have already passed through the tipping point.